Ruimtelijke mismatch, scholing en talenkennis in de Brusselse metropool: een analyse - Tobias Theys; Nick Deschacht; Stef Adriaenssens; Dieter Verhaest (Brussels Studies)
Spatial mismatch, where job seekers do not live where jobs can be found, can be an important barrier on the labour market, especially for vulnerable groups. In this study we look at the role that spatial mismatch plays in the Brussels metropolis. Using an improved benchmark, the distance-weighted spatial mismatch index, that also considers location-driven mismatch, we compare the spatial mismatch between the high- and low-skilled labour market and the labour market for the low-skilled with and without language skills. In the largest possible definition of the Brussels metropolis, results show a spatial mismatch of up to 50 % larger for the low-skilled, in comparison with the high-skilled. For the low-skilled without language skills, the spatial mismatch is 115 % higher than for the low-skilled with language skills. This difference is mainly due to a relative surplus of low-skilled job seekers (without language skills) in the Brussels-Capital Region and a relative shortage in the first belt of municipalities around the Region.